Compatibility of mixtures of phytosanitary products recommended for melon and their selectivity for Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) - Rafrana da Silva de Araújo, Karolina; Ferreira Rodrigues, Raimundo Henrique; Mesquita Fernandes, Antônia Karine; de Lima Almeida, Valentine; Sekiguchi de Godoy, Maurício; Pastori, Patrik Luiz (Revista Ceres, 2025)
In pest control, understanding insecticide compatibility and selectivity is crucial to effectively integrate the use of insecticides and parasitoids. The aim of this study was to evaluate the compatibility of mixtures of insecticides and fungicides recommended for melon and their selectivity in Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae). The were evaluated the compatibility of six mixtures: 1) Spinetoram + Pyraclostrobin and Fluxapyroxad; 2) Cyromazine + Pyraclostrobin and Fluxapyroxad; 3) Cyproconazole + Spinetoram; 4) Cyantraniliprole + Abamectin + Metiram and Pyraclostrobin; 5) Spinetoram + Azoxystrobin and Difenoconazole; 6) Abamectin + Cyantraniliprole; and a Control (distilled water). The compatible mixtures were applied to Anagasta kuehniella (Zeller, 1879) (Lepidoptera: Pyralidae) eggs, before and after T. pretiosum parasitism. Was evaluated: mortality of adult T. pretiosum females after exposure to treated eggs, parasitism, emergence and number of parasitoids emerged/egg. Only treatment 4 showed change in physical stability after 5 minutes. In selectivity tests, treatments 1, 3, and 5 caused greater mortality (>47%) of female adults. In pre-parasitism, parasitism (>77%) and emergence (>76%) were observed in all treatments, and all the mixtures were classified as innocuous to the parasitoid in these parameters. In post-parasitism, treatments affected negatively emergence (>51%) and number of parasitoids/egg at the three ages studied. Therefore, all mixtures were considered stable and viable for use with T. pretiosum, as long as they were applied before parasitoid releases.